Improving the Evacuation Time for 8-Story Office Building Using Pathfinder Simulation - Hadi Sutrisno, Himawan; Amiruddin, Jafar; ., Triyono (International Journal of Engineering and Technology, 2018)
The evacuation time during fire becomes the determining factor for survival and building occupants often ignore the knowledge and the correct way to evacuate during fire. This lack of knowledge increases panics among the evacuees and causes more casualties. By using the pathfinder simulation, the simulated evacuation time is compared with the real evacuation time to get the recommendation for the improvement of evacuation time to reach the assembly points. The improvement of the evacuation time is done by eliminating the time difference between the simulated evacuation time and the real evacuation time. This study may benefit the method to increase the evacuation ability and to improve the sterilization of the evacuation routes until the assembly points.